The influence of mood and information processing strategies on recall, persuasion, and intention to get a flu vaccine. Issue 1 (2nd January 2019) - Sar, Sela; Rodriguez, Lulu
Abstract: This study investigates the interactions between mood (positive/negative) and information processing style (item-specific/relational/narrative processing) on responses to three types of advertising messages (ungrouped list/grouped list/narrative ads). A mood congruency effect was postulated and found to influence recall, persuasion and behavioral intention. Results supported the hypothesis that message effectiveness was moderated by mood in the direction of congruency. That is, participants in a positive mood recalled more information, were more persuaded, and were more likely to adopt the recommended behavior after exposure to advertisements with a grouped list format. Evidence regarding similarity of factors influencing relational and narrative processing is presented.